SMART CHARGING DIGITAL ACCUMULATOR BASED ON ARDUINO UNO MICROCONTROLLER - Fadjar Bastari, Winarno; Prayogi, Aris (BEST, 2020)
The charging device usually uses a transformer and a diode bridge. Charging the battery is called direct charging. Because it does not have a safety for the battery it can cause heat to the battery. But over time, this is no longer effective, this work can be done digitally using a microcontroller.. However, this tool is still not perfect because at the time of testing it cannot be set, sooner or later, the charging is to cut time efficiency and there is no indicator that states that the charging is full or not. Therefore, based on the description above, the researcher aims to make a smart charging accumulator based on the Arduino Uno microcotroller that is smarter, more efficient and can be used easily, with the advantage of having a tap changer on the transformer that functions as a regulator of the output voltage. as desired and piezoelectric alarm as an indicator if a full charge or there is a problem with the equipment itself.